Library exceptions in the copyright laws of Ibero-American countries - Carlos Fernandez-Molina, Juan; Guimarães, José Augusto Chaves [UNESP] (Sage Publications Ltd, 2010)
The development of the digital setting has made it absolutely necessary to revise copyright legislation as a whole, including the exceptions that benefit libraries and similar institutions. Unfortunately, adaptation to the new technological reality is not taking place satisfactorily in most countries - the predominating trend is a refortification of copyright as opposed to user interests, and the maintenance of a certain pre-digital philosophy. In the case of Ibero-America the problem is twofold: aside from obsolescence or a lack of adaptation to the new technological setting, there are countries that have not yet included library-related exceptions in the national laws. Moreover, these happen to be developing countries, whose needs and interests do not coincide with those of the richer nations who paved the path to be followed by international treaties and copy- or copyright agreements. This study looks into the situation of exceptions to copyright to benefit libraries in the countries constituting Ibero-America, with a comparative analysis of the most significant characteristics of their national laws. It is concluded that it is crucial for these countries to take advantage of the options offered through the WIPO Copyright Treaty of 1996 and the results of the WIPO Development Agenda to update their legislation, in order that copyright will be respected, while at the same time making it easier for libraries to continue carrying out their social function in an adequate manner, always with the understanding of the developmental context of these countries.
Keywords: libraries; copyright; copyright exceptions; Ibero-America; developing countries